The main colouring substance and essential oil components of different carrot varieties - Takácsné Hájos, M. (International Journal of Horticultural Science, 1999)
Investigating colouring components it was found that the p carotene being the most important from the point of view of nutrition constitutes about 60-70% of the total colouring material, whereas the ratio of a carotene is 18-34%.Among the varieties having a short growing season the common incidence rate of the a and 13 carotene is very high (92.49 %), even a lower total colouring material content (178.02 ppm) results in bright orange red carrot roots.The incidence of a and carotene represents, however, only 84.24% of the similar total colouring material value (171.74 ppm) measured in Nantais.Among the storage varieties Fertődi vörös has the highest value of total colouring substance (213.04 ppm) from which the common proportion of the two carotene (a and (3) compounds amounts to 93.77%.When testing the essential oil components the cariophyllen shows the highest incidence rate, which has a negative influence on the flavour materials of the carrot. Among the early varieties in Nantais Forto this quantity amounts to 24.08 ppm which is almost twice as much as the amount measured in Nantais. We found a similarly unfavourable quantity in %lords &ids (25.47 ppm).Looking at the beta-pinen and 1-limonen of a bactericidal effect the quantity of l-limonen is higher (1.36 ppm on the average of the varieties). Among the varieties that have a longer growing season and which are suitable for processing Fertődi vörös is the best in terms of essential oil and colour content. Its beta-pinen content was above the average of this variety (1.12 ppm) while its 1-limonen content was considerably high (1.26 ppm).